2013
DOI: 10.1002/term.1744
|View full text |Cite
|
Sign up to set email alerts
|

FGF, TGFβand Wnt crosstalk: embryonic toin vitrocartilage development from mesenchymal stem cells

Abstract: Articular cartilage is easily damaged, yet difficult to repair. Cartilage tissue engineering seems a promising therapeutic solution to restore articular cartilage structure and function, with mesenchymal stem cells (MSCs) receiving increasing attention for their promise to promote cartilage repair. It is known from embryology that members of the fibroblast growth factor (FGF), transforming growth factor-β (TGFβ) and wingless-type (Wnt) protein families are involved in controlling different differentiation stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 131 publications
(190 reference statements)
1
54
0
1
Order By: Relevance
“…There is also research that had found that TGF- β 1 always played an essential role in chondrocyte maturation. TGF- β 1 stimulated chondrocytes proliferation but inhibited chondrocyte differentiation [19]. Recently in order to induce chondrocytes repair of the damaged cartilage several investigations have focused on how to deliver TGF- β 1 to damaged articular cartilage in vivo [20].…”
Section: Discussionmentioning
confidence: 99%
“…There is also research that had found that TGF- β 1 always played an essential role in chondrocyte maturation. TGF- β 1 stimulated chondrocytes proliferation but inhibited chondrocyte differentiation [19]. Recently in order to induce chondrocytes repair of the damaged cartilage several investigations have focused on how to deliver TGF- β 1 to damaged articular cartilage in vivo [20].…”
Section: Discussionmentioning
confidence: 99%
“…Intramembranous ossification primarily takes place at both ends of bony callus, and new bones are formed by proliferation of periosteal osteoblasts [2, 3]. The process of fracture healing is completed as callus is remodeled, with functions of both osteoclasts and osteoblasts according to appropriate mechanical requirements [4, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…TGF‐β, a pleiotropic cytokine, is involved in the regulation of cell division and suppression of immune response 55. Upon binding of TGF‐β to its receptor, the receptor complex recruits and phosphorylates the carboxy terminus of receptor‐regulated Smad proteins (R‐Smads: Smad2 and Smad3) 36, 56. Phosphorylated Smads can interact with Smad4 to become a complex, and this complex translocates into the nucleus and turns on gene transcription 55.…”
Section: Discussionmentioning
confidence: 99%